2023
DOI: 10.3390/life13041026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Seaweed Polysaccharides in Gastrointestinal Health: Protective Effect against Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a prominent global public health issue. Anti-inflammatory medications, immunosuppressants, and biological therapies are currently used as treatments. However, they are often unsuccessful and have negative consequences on human health. Thus, there is a tremendous demand for using natural substances, such as seaweed polysaccharides, to treat IBD’s main pathologic treatment targets. The cell walls of marine algae are rich in sulfated polysaccharides, including carrageenan in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 125 publications
0
10
0
Order By: Relevance
“…These findings underscore the potential of diverse marine alga extracts to manifest anti-inflammatory and anticolitis effects. Moreover, the extensive research substantiating these effects necessitates continued exploration of compounds derived from alga extracts [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings underscore the potential of diverse marine alga extracts to manifest anti-inflammatory and anticolitis effects. Moreover, the extensive research substantiating these effects necessitates continued exploration of compounds derived from alga extracts [16].…”
Section: Discussionmentioning
confidence: 99%
“…The recent direction of IBD etiological research has ushered in the potential for innovative therapeutic modalities, including naturally occurring compounds. These compounds proffer the prospect of redressing perturbations in the gut microbiome while simultaneously expediting the restorative process of the mucosal layer [15,16]. Among such natural compounds, complex marine polysaccharides have been extensively studied as pharmaceuticals [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…They do this by slowing down the absorption of glucose from the digestive tract, thereby reducing the peak glucose levels that occur after a meal. This can help to prevent sudden spikes in blood sugar levels, which are common in people with diabetes [70,78].…”
Section: Polysaccharides As Glycemic Modulatorsmentioning
confidence: 99%
“…Seaweed compounds have shown promise in this regard, as many of them have been found to have activity against multiple targets. For example, fucoidan, a sulfated polysaccharide found in brown seaweeds, has been shown to have anti-inflammatory, anticancer, and antiviral properties, as well as potential for the treatment of diabetes and cardiovascular disease [78,127].…”
Section: Potential For the Development Of New Multitarget Drugs From ...mentioning
confidence: 99%
“…Recently, there has been an increasing trend towards the application of seaweed-derived bioactive compounds in the food and functional food industries [ 5 ]. Sulfated polysaccharides from brown seaweed are renowned for various biological activities, such as antioxidant, anti-inflammatory, and cosmeceutical activities [ 6 ]. Most earlier studies have reported that the sulfated polysaccharide fucoidan from brown seaweeds possesses multifunctional, non-toxic, and highly biocompatible polymers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%